Healing children's grief : surviving a parent's death from cancer - Christ, Grace Hyslop (Oxford University Press, 2000)
This work identifies five developmentally derived age groups that clarify important differences in children's grief and mourning processes, in their understanding of events, their interactions with families, and their varying needs for help and support.